2019
DOI: 10.7196/samj.2019.v109i6.13700
|View full text |Cite
|
Sign up to set email alerts
|

Audit of diabetic ketoacidosis management at a tertiary hospital in Johannesburg, South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…This is most likely due to the heightened hormonal response with increased insulin resistance that predisposes pregnant woman with diabetes to the development of DKA. Contrary to the findings of a recent South African audit of DKA in the general population by Thomas et al, 17 reporting that DKA mostly presented with moderate severity, the study found that the majority of the patients presented with mild DKA in pregnancy and 14.2% patients presented with euglycemic DKA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is most likely due to the heightened hormonal response with increased insulin resistance that predisposes pregnant woman with diabetes to the development of DKA. Contrary to the findings of a recent South African audit of DKA in the general population by Thomas et al, 17 reporting that DKA mostly presented with moderate severity, the study found that the majority of the patients presented with mild DKA in pregnancy and 14.2% patients presented with euglycemic DKA.…”
Section: Discussioncontrasting
confidence: 99%
“…In low-to middle-income countries there are patient and healthcare system factors that are associated with a negative impact on management of diabetes, especially DKA. [14][15][16][17][18][19][20][21] Poor compliance with insulin therapy, poor prenatal attendance, and poor recognition of sick days are identifiable patient factors, but these should not influence the emergency inpatient management of DKA. [12][13][14][15][16][17][18][19][20][21] Healthcare systems are overburdened with the ever-increasing numbers of women with high-risk pregnancies, including DKA in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery time was delayed by 76% among severe DKA adult patients as compared with mild DKA adult patients. This finding is supported by the study conducted in South Africa identifies severe DKA was correlated with a longer time to resolution (28). The possible reason in this study could be due to the disease pathophysiology, patients with severe DKA had more electrolyte abnormalities compared with the mild and moderate forms of the disease(48) which is supported with a study conducted in Australia showed that higher admission potassium levels are independent predictors of a slower time to resolution of DKA(30).…”
Section: Discussionsupporting
confidence: 65%
“…Even though DKA patients with appropriate treatment are expected to make a full recovery within 24 hours (9, 11, 14, 15) the resolution time of DKA is longer in African countries. For example in South Africa the average time to resolution of DKA was 21 hours; excluding severe DKA, mild and moderate DKA had an average time to resolution of 20 hours (28) and in Kenya, the median time to resolution was 59 hours(29).…”
Section: Introductionmentioning
confidence: 99%